Right to Education of the Disabled - Shah, Justice Ajit Prakash (JOURNAL OF INDIAN EDUCATION, 2014)
The present lecture tries to demonstrate as to how persons with disabilities have been neglected in India, both by the society as well as by the government. The desire of such persons with disabilities to join the mainstream way of life remains a distant dream for now as the present mechanisms and policies in place are grossly inadequate to effect any real change in the current scenario. It is in this light that this lecture discusses the right of disabled children to receive education for their overall development since this right is a fundamental right that is available to every child, including the ones with any form of disability. However, any reformatory measures in this area are seriously impeded by a lack of a standardised and uniformly accepted definition of disability in India, leading to varying and incorrect estimates in identifying children with special needs. Different data bases have their own parameters of judging and identifying disability, leading to large discrepancy in figures.